Development of a Capacitance Sensor System to Measure Ultra-Low Water Content in Crude Oil - Ling, Lim Yee (Universiti Teknologi PETRONAS, 2014)
The capacitance sensor system had been applied in various applications including measurement of water content in crude oil. The purity of crude oil is graded based on the water content found in it. The lesser the amount of water detected, the higher the purity of crude oil. The determination of water content is crucial as it directly reflects the quality of crude oil. However, the capacitance sensor system is limited to a high water concentration measurement. In this project, a higher resolution measurement is introduced which utilizes the capacitance sensor system based on phase angle conversion. The presence of water inside the crude oil is indicated by the change in capacitance value and results in a phase shift. The sensor system is capable of detecting a very small change of capacitance, meaning it is able to measure ultra-low water content inside the crude oil.